DESCRIPTION OF NURSES QUALITY OF WORK LIFE IN RSUD DR. M.M. DUNDA LIMBOTO - Suci Tasya Amelia Kau; Wirda Y. Dulahu; Dewi Suryaningsi Hiola (Jambura Journal of Health Sciences and Research, 2022)
Most health workers in hospitals are nurses who have an important responsibility in providing health services. Quality of work life is an important issue in health organizations, has several impacts on nurses and nursing services. The low quality of work life of nurses can lead to feelings of frustration, incompetence, and feelings of guilt. If it continues, it can lead to an incident of turnover for nurses. Quality of Nursing Work Life (QNWL) is an important element for the nursing profession that will affect the quality of health services. The purpose of this study was to determine the quality of working life of nurses in RSUD Dr. M.M. Dunda Limboto.This research is a type of quantitative research using descriptive analysis with a cross-sectional approach. The research population of nurses was 272 people with a sample of 161 respondents using proportionate stratified random sampling technique. Data analysis using univariate test.The results showed that nurses who had a good quality of work life amounted to 124 respondents (77%), had a sufficient quality of work life amounted to 30 respondents (18.6%) and had a poor quality of work life amounted to 7 respondents (4.3%). Quality of working life of nurses in RSUD Dr. M.M Dunda Limboto was mostly in the good category with a percentage of 77%. This research is expected to be an input for hospitals in improving the quality of nurses' work so that they can provide optimal health services.